2000
DOI: 10.5432/jjpehss.kj00003397590
|View full text |Cite
|
Sign up to set email alerts
|

Muscular activity pattern during sprint running

Abstract: The muscular activity pattern, function and maximal contraction velocity during the starting dash and sprint running at maximal velocity were studied, The subjects were five adult male sprinters, whose sprint running moyements in the sagittal plain were analyzecl (100 fps) from videotape recordings made with a high-speed camera, The ground reaction forces and EMGs of eight leg muscles were also recorded, Changes in length from the origin to the insenion (muscle-tendon complex: MTC) of the eight leg muscles wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…During acceleration of sprint running, the hip extension torque is exerted from the late-swing to early-stance phase, i.e., around foot contact (Baba et al, 2000;Johnson and Buckley, 2001), and the hip ‰exion angle at the foot contact is ¿809at the second step of 40-m sprint running (Jacobs and van Ingen Schenau, 1992) and ¿409even at the 60-m point of sprint running (Ito et al, 1997). On the other hand, the adductor magnus muscle acts as a hip extensor through the whole range of hip joint motion and the adductor brevis and the adductor longus muscles also act as hip extensors when the hip joint is ‰exed more than 259and 509 , respectively (Dostal et al, 1986).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During acceleration of sprint running, the hip extension torque is exerted from the late-swing to early-stance phase, i.e., around foot contact (Baba et al, 2000;Johnson and Buckley, 2001), and the hip ‰exion angle at the foot contact is ¿809at the second step of 40-m sprint running (Jacobs and van Ingen Schenau, 1992) and ¿409even at the 60-m point of sprint running (Ito et al, 1997). On the other hand, the adductor magnus muscle acts as a hip extensor through the whole range of hip joint motion and the adductor brevis and the adductor longus muscles also act as hip extensors when the hip joint is ‰exed more than 259and 509 , respectively (Dostal et al, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…Considering from the previous reports, it is hypothesized that, among the lower limb muscles, muscularity of the hamstrings, the quadriceps femoris, and the triceps surae muscles is important as they are agonist muscles in hip extension, knee extension and plantar ‰exion, respectively. The hip extension torque exerted through the mid-swing phase to early-stance phase in an acceleration of sprint running is accompanied by the electromyographic activity of the biceps femoris muscle (Baba et al, 2000). In addition, it has been reported that a great part of hip extension work done in push-oŠ phase of sprint acceleration was accounted by the hamstrings (e.g., Jacobs et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…According to the previous findings (Baba et al., 2000; Struzik et al., 2015), the maximal angular velocity of ankle dorsiflexion during sprinting and jumping was around 500–600 deg·s −1 . Moreover, we previously reported that the active muscle stiffness measured at a low angular velocity (peak angular velocity was 250 deg·s −1 ) in long‐distance runners was significantly greater than that in untrained men (Kubo et al., 2015).…”
Section: Discussionmentioning
confidence: 64%
“…The present results on active muscle stiffness at 200 and 300 deg·s −1 agree with our previous finding. Active muscle stiffness reported by Kubo et al (Kubo, Miyazaki, et al., 2017) represented an intrinsic muscle property without any potential neural effects, since the analyzed period (60‐ms from the onset of stretch) was selected to avoid modifying by the stretch reflex (Allum & Mauritz, 1984; Baba et al., 2000; Kubo, 2014). In this study (Kubo, Miyazaki, et al., 2017), we speculated that active muscle stiffness modified by the stretch reflex in sprinters would be greater than that in untrained men.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation